Chemical Sensitization of Apoptosis Induced by Hyperthermia - KAMEDA, KEISUKE; ARAI, YOKO; ZHAO, QING-LI; LI, FU-JUN; YUKI, HIROYOSHI; KONDO, TAKASHI; TANABE, KIYOSHI (Japanese Journal of Hyperthermic Oncology, 2000)
Hyperthermia (HT) has been recognized as an effective and attractive tool in anticancer therapy. However, the results obtained in therapy by HT alone have been only partially satisfactory. Consequently, attention has focused on the search for substances able to sensitize tumor cells to the damage caused by HT without reducing the capacity of normal cells. It has been reported that the tumor cell death in HT is mediated by apoptosis. Activation of a preprogrammed cascade of molecular events will result in DNA degradation and nuclear fragmentation, leading to apoptosis. However, the pathways which can induce apoptosis varies in different cells. If we could discover common stimuli which could induce apoptosis in all types of cells, we would obtain a new anticancer therapy against all types of tumor cells. In this report, we overviewed both mechanisms of HT-induced apotosis, and the substances used to enhance HT-induced apoptosis. Moreover, we provide evidence for the role of intracellular Ca2+concentration in HT-induced apoptosis.